Pemantauan status gizi balita di Kota Yogyakarta: metode pelaksanaan, tantangan, dan persepsi ibu balita tentang posyandu selama pandemi COVID-19 - Rachmawati Widyaningrum; Annisa Parisudha; Yuni Wahyuningsih Setiawan; Nurfaizah Jawardi; Nur Hurriah Nabila Faras (Jurnal Gizi Klinik Indonesia, 2022)
Background: COVID-19 pandemic brings a higher risk of malnutrition because of the economic crisis that emphasizes the importance of child nutritional status monitoring during the pandemic. However, nutrition-related care in health care faces several challenges to the social limitation policy for preventing virus spreading. Challenges include delivery, coordination, and follow-up methods. In addition, the mothers' perception concerning the importance of nutritional status monitoring also becomes the determinant of their participation.Objectives: This research aimed to explore the implementation method, challenges, and mothers' perception of the children's nutritional status monitoring process during a pandemic through “posyandu” by applying health protocols.Methods: This research is a descriptive qualitative study in which the data were collected using in-depth interviews. The respondents in this study were mothers of a child aged 0-5 years who lived in Yogyakarta and participated actively in Posyandu. Data triangulation was applied by interviewing the cadres of posyandu and nutritionists in Health Care or Office in Yogyakarta. Results: The posyandu delivered the measurements by adjusting the method with an invitation divided into several measurement sessions or a door-to-door system to minimize crowd. The obstacles faced were the need to procure medical devices and ensure the validity of the data obtained. Conclusions: Child nutritional status monitoring during the COVID-19 pandemic was conducted by applying COVID-19 safety protocols according to the recommendations of the Indonesian Ministry of Health. There should be sufficient support from stakeholders to help posyandu overcome the obstacles: the procurement of medical equipment to meet the health protocol requirements. In addition, there is a need to improve parents' skills in measuring child anthropometric measurements through education and guidelines.